Netting material with adhesion prevention, self-cleaning and toughness and application of netting material

By using a three-layer-structured mesh material, combined with antibacterial polyethylene core layer, ultra-thin strong magnetic film, and H-SiO2@CIP Silicane microcontroller, solve the poor anti-adhesion effect of the existing net clothes materials, poor anti-adhesion effect, The short service life and environmental protection issues have improved the improvement of high -efficiency and fade, flexibility, and tensile resistance and resistance.

CN119369808AActive Publication Date: 2025-01-28GUANGDONG OCEAN UNIVERSITY

Patent Information

Application Number
CN202411256177.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-28
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The existing mesh clothing materials have problems such as poor anti-adhesion effect, short service life, insufficient wind and wave resistance and erosion resistance in marine aquaculture. Traditional anti-fouling coatings have poor flexibility, low tensile and twist resistance strength, and contain Copper antifoulants are not environmentally friendly.

Method used

The three-layer-structured mesh material, including antibacterial polyethylene core layer, ultra-thin magnetic film, and surface with an epoxy resin layer with H-SIO2@CIP Silicane microstructure. Antibacterial substances are released through antibacterial polyethylene core layers. The ultra-thin and strong magnetic film helps the coating formation, and builds a hydrophobic surface through the H-SIO2@CIP Silicane microstructure to improve the anti-adhesion and self-cleaning effect.

Benefits of technology

The anti -adhesion of mesh materials is coming from the cleaning effect. It is excellent and flexible in the anti -pollution prevention period, good flexibility, high tensile and anti -distortions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119369808A_ABST
    Figure CN119369808A_ABST
Patent Text Reader

Abstract

The invention provides a netting material with adhesion prevention, self-cleaning and toughness, and belongs to the technical field of netting materials for breeding. The invention provides a netting material with anti-adhesion, self-cleaning and toughness. The netting material comprises an antibacterial polyethylene core layer, an ultrathin strong magnetic film and an epoxy resin layer, wherein the surface of the epoxy resin layer is provided with an H-SiO2 coated CIP silane microstructure; the antibacterial polyethylene core layer can release antibacterial substances for preventing marine bacteria or attached microorganisms, and the ultrathin strong magnetic film can slowly permeate the antibacterial substances to the outermost layer; the nano-iron particle-silane microstructure coated with hydrophobic modified silicon dioxide and constructed on the outer surface of the epoxy resin coating has high hydrophobicity and adhesion resistance, the self-cleaning antifouling effect is achieved, antibacterial molecules released by the antibacterial polyethylene core layer are further slowly permeated to the outside, and waste is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of net materials for aquaculture, and in particular to a net material with the characteristics of anti-adhesion, self-cleaning and toughness and application thereof. Background Art

[0002] In the marine aquaculture industry, fish are usually cultured in cages, and the net material is the key basic material for making the cage. Traditional net materials are made of synthetic fibers, such as nylon, polyethylene, polypropylene, etc. Although synthetic fibers have good corrosion resistance and toughness, traditional net materials have the following defects: 1. Marine biological fouling; 2. Poor resistance to wind and waves and erosion; 3. Short service life of the net (about 1 year); 4. Synthetic fibers cannot be recycled and are not environmentally friendly. Among them, marine biofouling refers to the accumulation of microorganisms, plant organisms, and animal organisms in the ocean on artificial surfaces. After a large number of marine organisms attach to the deep-sea cages used for aquaculture, the mesh is blocked, the convection of seawater inside and outside the cages is reduced, and the content of dissolved oxygen and the supply of food are reduced, causing the farmed seafood to develop poorly or even die, seriously affecting the output and quality of seafood.

[0003] At present, the marine aquaculture industry often uses physical removal, antifouling agents and biological control methods to control biofouling. Physical removal methods usually use a variety of methods such as regular net replacement, mechanical cleaning, antifouling or cage rotation design and chemical control agents to deal with the problem of fishing net fouling. The process is cumbersome and labor-intensive, time-consuming and labor-intensive, repeated many times, damage to the cage, and also affect the aquaculture cycle of seafood. The use of biological control technology to solve the problem of marine biological fouling has huge potential market value, but the high cost limits its application in the marine aquaculture industry. The use of net antifouling coating is the current mainstream antifouling method. Antifouling coating is usually applied to fishing nets by dipping. The antifouling period of nets in marine aquaculture is required to be at least six months. However, the net antifouling coating in the prior art has poor flexibility. After covering the net, the tensile and torsional strengths are significantly reduced, affecting the normal operation of the net. In addition, due to the limited antifouling effect of film-forming substances, a large amount of copper antifouling agents are often added to the net antifouling coatings on the market to achieve antifouling performance, which does not meet environmental protection requirements and also poses potential risks to aquatic organisms. Therefore, providing an environmentally friendly aquaculture net with excellent anti-fouling effect, good flexibility, high tensile strength and high torsional strength is a technical problem that needs to be solved urgently in the prior art. Summary of the invention

[0004] The purpose of the present invention is to provide a net material with anti-adhesion, self-cleaning and toughness and its application. The net material with anti-adhesion, self-cleaning and toughness provided by the present invention has anti-adhesion and self-cleaning effects. The aquaculture net prepared from the net has excellent anti-fouling effect, good flexibility, high tensile strength and high torsional strength.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a mesh material with both anti-adhesion, self-cleaning and toughness, including a three-layer structure, which includes an antibacterial polyethylene core layer, an ultra-thin strong magnetic film and a surface-mounted H-SiO 2 @CIP silane microstructured epoxy resin layer;

[0007] The preparation method of the net material comprises the following steps:

[0008] S1, preparing an antibacterial polyethylene core layer;

[0009] S2, coating the antibacterial polyethylene core layer obtained in step (S1) with the ultra-thin ferromagnetic film to obtain a coated antibacterial polyethylene core layer;

[0010] S3, coating the epoxy resin mixed solution on the surface of the coated antibacterial polyethylene core layer obtained in the step (S2), and drying to obtain a net material having both anti-adhesion, self-cleaning and toughness.

[0011] Preferably, the diameter of the antibacterial polyethylene core layer is 1 to 3.5 mm, the thickness of the ultra-thin strong magnetic film is 2 to 400 μm, and the surface is provided with H-SiO 2 @The thickness of the epoxy resin layer of the CIP silane microstructure is 80 to 260 μm.

[0012] Preferably, the method for preparing the antibacterial polyethylene core layer in step (S1) comprises the following steps:

[0013] (1) premixing polyethylene, an antibacterial agent, succinic anhydride and dicumyl peroxide, and then sequentially performing blending, grafting reaction and extrusion granulation to obtain antibacterial polymer particles;

[0014] (2) The antibacterial polymer particles obtained in step (1) are premixed with PET resin, phenolic antioxidant, and maleic anhydride grafted polyethylene, and then kneaded and extruded into granules in sequence, and then melt-extruded from the spinneret holes of a spinneret by a single-screw extruder, and melt-spinned and stretched to obtain an antibacterial polyethylene core layer.

[0015] Preferably, the antibacterial agent in step (1) is at least two of polyhexamethylene monoguanidine phosphate, polyhexamethylene biguanide phosphate, and streptomycin.

[0016] Preferably, the step (S3) comprises the following steps:

[0017] (S3-1) mixing a suspension of polydimethylsiloxane, a crosslinking agent and nano-iron particles coated with hydrophobically modified silica, and then sequentially performing a first stirring, a first vacuum degassing and an ultrasonic treatment to obtain a mixed solution;

[0018] Adding bisphenol epoxy resin to the mixed solution, and sequentially performing a second stirring and a second vacuum defoaming to obtain an epoxy resin mixed solution;

[0019] (S3-2) coating the epoxy resin mixed solution obtained in the step (S3-1) on the surface of the coated antibacterial polyethylene core layer obtained in the step (S2), and drying to obtain a mesh material having anti-adhesion, self-cleaning and toughness.

[0020] Preferably, the method for preparing the hydrophobically modified silica-encapsulated nano-iron particles in step (S3-1) comprises the following steps:

[0021] The silicon dioxide-coated nano-iron particles are dispersed in an alkaline ethanol solution, dried, and then subjected to plasma modification treatment to obtain activated silicon dioxide-coated nano-iron particles;

[0022] The activated silica-wrapped nano-iron particles are mixed with dimethyldichlorosilane (DCDMS) and toluene, and then subjected to a hydrolysis reaction. A KH-560 silane coupling agent is then added to carry out a coupling reaction to obtain hydrophobically modified silica-wrapped nano-iron particles.

[0023] Preferably, the plasma modification treatment lasts for 2 to 5 minutes, and the concentration of oxygen in the gas used for the plasma modification treatment is 50 vt% to 70 vt%.

[0024] Preferably, in the step (S3-1), the mass ratio of polydimethylsiloxane, crosslinking agent, and hydrophobically modified silica-wrapped nano-iron particles is 15:(2-8):(6-12).

[0025] Preferably, the drying temperature in the step (S3-2) is 45 to 55°C, and the drying time is 16 to 20 hours.

[0026] The present invention also provides the use of the net material with both anti-adhesion, self-cleaning and toughness as described in the above technical solution in the preparation of aquaculture nets, comprising the following steps:

[0027] A plurality of strands of the net material are braided to form a net rope, and the net rope is woven to form a knotless mesh sheet, so as to obtain a breeding net with anti-adhesion, self-cleaning and toughness.

[0028] The present invention provides a mesh material with both anti-adhesion, self-cleaning and toughness, including a three-layer structure, which includes an antibacterial polyethylene core layer, an ultra-thin strong magnetic film and a surface-mounted H-SiO 2@CIP Silane Microstructured Epoxy Resin Layer. The present invention utilizes the antibacterial polyethylene core layer to release antibacterial substances that prevent marine bacteria or attached microorganisms; the ultra-thin strong magnetic film, on the one hand, helps to coat the epoxy resin coating that forms the outermost layer, thereby constructing a hydrophobically modified silica-wrapped nano-iron particle-silane microstructure on the outer surface, and on the other hand, slowly penetrates the antibacterial substances released by the antibacterial polyethylene core layer into the outermost layer; the hydrophobically modified silica-wrapped nano-iron particle-silane microstructure (abbreviated as H-SiO 2 @CIP silane microstructure) has high hydrophobicity and anti-adhesion, giving it self-cleaning and anti-fouling effects, and further slowly permeating the antibacterial molecules released by the antibacterial polyethylene core layer to the outside to avoid waste; the present invention utilizes an antibacterial polyethylene core layer, an ultra-thin strong magnetic film and a surface with H-SiO 2 The three-layer structure formed by the epoxy resin layer of the @CIP silane microstructure maintains the flexibility of the mesh material with both anti-adhesion, self-cleaning and toughness, and improves its tensile and torsional strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A schematic diagram of the structure of a net material with both anti-adhesion, self-cleaning and toughness provided by the present invention;

[0030] Figure 2 The outer surface of the epoxy resin layer in the present invention is constructed with hydrophobically modified silica-coated nano-iron particles-silane microstructure diagram, wherein the left figure is a surface microstructure diagram, and the right figure is a partial enlarged diagram;

[0031] Figure 3 The nano iron particles encapsulated by the hydrophobically modified silica in the present invention are H-SiO 2 @Schematic diagram of the structure of CIP particles. DETAILED DESCRIPTION

[0032] The present invention provides a mesh material with both anti-adhesion, self-cleaning and toughness, including a three-layer structure, which includes an antibacterial polyethylene core layer, an ultra-thin strong magnetic film and a surface-mounted H-SiO 2 @CIP silane microstructured epoxy resin layer;

[0033] The preparation method of the net material comprises the following steps:

[0034] S1, preparing an antibacterial polyethylene core layer;

[0035] S2, using coating technology and adhesive, the ultra-thin strong magnetic film is coated with the antibacterial polyethylene core layer obtained in step (S1) to obtain a coated antibacterial polyethylene core layer;

[0036] S3, coating the epoxy resin mixed solution on the surface of the coated antibacterial polyethylene core layer obtained in the step (S2), and drying to obtain a net material having both anti-adhesion, self-cleaning and toughness.

[0037] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.

[0038] In the present invention, the diameter of the antibacterial polyethylene core layer is preferably 1 to 3.5 mm, more preferably 1.3 to 3 mm; the thickness of the ultra-thin strong magnetic film is preferably 2 to 400 μm, more preferably 10 to 300 μm, and the surface is provided with H-SiO 2 The thickness of the epoxy resin layer of the @CIP silane microstructure is preferably 80 to 260 μm, more preferably 100 to 230 μm.

[0039] In the present invention, the method for preparing the antibacterial polyethylene core layer in step (S1) comprises the following steps:

[0040] (1) premixing polyethylene, an antibacterial agent, succinic anhydride and dicumyl peroxide, and then sequentially performing blending, grafting reaction and extrusion granulation to obtain antibacterial polymer particles;

[0041] (2) The antibacterial polymer particles obtained in step (1) are premixed with PET resin, phenolic antioxidant, and maleic anhydride grafted polyethylene, and then kneaded and extruded into granules in sequence, and then melt-extruded from the spinneret holes of a spinneret by a single-screw extruder, and melt-spinned and stretched to obtain an antibacterial polyethylene core layer.

[0042] In the present invention, the molecular weight of the polyethylene is preferably 100,000 to 500,000, more preferably 200,000 to 400,000.

[0043] In the present invention, the antibacterial agent is at least two of polyhexamethylene monoguanidine phosphate, polyhexamethylene biguanide phosphate, and streptomycin; the antibacterial agent preferably accounts for 15% to 50% of the mass of the polyethylene, and more preferably 20% to 40%; the mass of the succinic anhydride preferably accounts for 8% to 12% of the mass of the polyethylene; the mass of the diisopropyl peroxide initiator preferably accounts for 1% to 1.5% of the mass of the polyethylene.

[0044] In the present invention, the temperature of the blending is preferably 180-230°C, more preferably 200-220°C. The present invention has no special restrictions on the time of the blending, as long as the components are mixed evenly. In the present invention, the temperature of the grafting reaction is preferably 190-240°C, more preferably 200-220°C; the time of the grafting reaction is preferably 1-8h, more preferably 2-6h. The present invention controls the temperature and time of the grafting reaction within the above range to ensure that more polyhexamethylene monoguanidine phosphate / polyhexamethylene biguanide phosphate and streptomycin are grafted onto polyethylene to obtain antibacterial polymer particles with excellent antibacterial effect.

[0045] In the present invention, the particle size of the antibacterial polymer particles is preferably 1 to 10 mm, more preferably 2 to 5 mm.

[0046] In the present invention, the mass ratio of the antibacterial polymer particles to the PET resin and the maleic anhydride grafted polyethylene is preferably 1:(1-3):(1-3), more preferably 1:(1.2-2.5):(1.2-2.5).

[0047] In the present invention, the molecular weight of the PET resin is preferably 100000 to 180000. In the present invention, the maleic anhydride grafted polyethylene is maleic anhydride grafted PE of model ADDIMER 630R produced by CERONAS of Germany. In the present invention, the mass of the phenolic antioxidant accounts for 0.05% to 0.6% of the mass of the antibacterial polymer particles; the phenolic antioxidant is one or more of 2,6-di-tert-butyl-4-methylphenol, β-(4-hydroxy-3,5-di-tert-butylphenyl) propionic acid n-octadecanoic acid alcohol ester, tert-butylphenol hydroxybenzoate, p-hydroxybenzoate, tri-tert-butyl hydroxybenzoate.

[0048] In the present invention, the kneading time is preferably 1 to 3 hours.

[0049] In the present invention, the pore size of the spinneret is preferably 1.00 mm to 3.00 mm; the process conditions of the melt spinning and stretching treatment are preferably: the spinning temperature is 230 to 360°C, the spinning speed is 3 to 25 m / min, the stretching multiple is 2 to 55 times, and the stretching temperature is 60 to 150°C.

[0050] In the present invention, the preparation method of the ultra-thin strong magnetic film preferably includes: mixing 40 to 80 parts of resin particles, 20 to 40 parts of magnetic powder and 1 to 10 parts of dispersant to obtain surface pretreated particles; extruding and granulating the surface pretreated particles in a twin-screw extruder to obtain masterbatches; processing the masterbatches through a blow molding machine to obtain an ultra-thin strong magnetic film.

[0051] In the present invention, the diameter of the magnetic powder is 1 to 20 nm; the magnetic powder is preferably at least one of barium ferrite, cobalt ferrite, ferroferric oxide, gamma iron oxide, carbonyl iron powder, manganese zinc ferrite, nickel oxide, cobalt oxide and iron powder. In the present invention, the resin particles are preferably one or more of polyethylene, polyvinyl chloride, ethylene-vinyl alcohol copolymer, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer and ethylene-methacrylic acid copolymer. In the present invention, the dispersant is preferably at least one of KH-560 silane coupling agent, KH-570 silane coupling agent, KH-151 silane coupling agent and KH-171 silane coupling agent.

[0052] In the present invention, the parameters of the twin-screw extruder are preferably: a heating temperature of 120 to 190° C., a screw speed of 180 to 330 r / min, and a feeding speed of 40 to 55 r / min.

[0053] In the present invention, the parameters of the blow molding machine are preferably: heating temperature of 120-210° C., screw speed of 80-120 r / min, blow ratio of 1:(1-3), and traction speed of 4-8 m / min.

[0054] In the present invention, the coating method is preferably to use coating technology and adhesive to tightly adhere the ultra-thin strong magnetic film to the surface of the antibacterial polyethylene core layer.

[0055] The present invention has no special limitation on the laminating technology, and any technical solution known in the art can be used. In the present invention, the adhesive is preferably at least one of polyurethane emulsion, vinyl polyurethane emulsion, polyisocyanate emulsion, and blocked polyurethane emulsion.

[0056] In the present invention, the epoxy resin mixed solution is coated on the surface of the coated antibacterial polyethylene core layer, and then dried to obtain a net material having both anti-adhesion, self-cleaning and toughness, which preferably includes the following steps:

[0057] (S1) mixing a suspension of polydimethylsiloxane, a crosslinking agent and nano-iron particles coated with hydrophobically modified silica, and then sequentially performing a first stirring, a first vacuum degassing and an ultrasonic treatment to obtain a mixed solution;

[0058] Adding bisphenol epoxy resin to the mixed solution, and sequentially performing a second stirring and a second vacuum defoaming to obtain an epoxy resin mixed solution;

[0059] (S2) coating the epoxy resin mixed solution obtained in the step (S2) on the surface of the coated antibacterial polyethylene core layer, and drying the mixture to obtain a double-layer membrane structure.

[0060] In the present invention, the molecular weight of the polydimethylsiloxane is preferably 1500 to 8000, more preferably 2000 to 6000. In the present invention, the crosslinking agent is preferably at least one of methyltri(methoxy)silane, vinyltrimethoxysilane, and 3-aminopropyltrimethoxysilane.

[0061] In the present invention, the ethyl acetate suspension of the hydrophobically modified silica-wrapped nano-iron particles is preferably obtained by mixing the hydrophobically modified silica-wrapped nano-iron particles with ethyl acetate and subjecting the mixture to ultrasound.

[0062] In the present invention, the mass ratio of the polydimethylsiloxane, the crosslinking agent, and the hydrophobically modified silica-wrapped nano-iron particles is preferably 15:(2-8):(6-12), and more preferably 15:(3-6):(8-11).

[0063] The present invention has no particular limitation on the first stirring method, as long as the ethyl acetate is fully volatilized. In the present invention, the ultrasonic time is preferably 10 to 20 minutes.

[0064] In the present invention, the concentration of the bisphenol epoxy resin in the epoxy resin mixed solution is preferably 50wt% to 70wt%; the bisphenol epoxy resin is preferably at least one of bisphenol A epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin and bisphenol A novolac epoxy resin.

[0065] In the present invention, the second stirring time is preferably 30 to 50 minutes.

[0066] In the present invention, the coating method is preferably spin coating; the coating thickness is preferably 130 to 250 μm, more preferably 150 to 230 μm.

[0067] In the present invention, the drying temperature is preferably 45 to 55° C., and the drying time is 16 to 20 hours.

[0068] In the present invention, the method for preparing the hydrophobically modified silica-encapsulated nano-iron particles preferably comprises the following steps:

[0069] The alkaline ethanol solution of the silicon dioxide-coated nano-iron particles is dried and then subjected to plasma modification treatment to obtain activated silicon dioxide-coated nano-iron particles;

[0070] The activated silicon dioxide-wrapped nano-iron particles are mixed with dimethyldichlorosilane and toluene, and then subjected to a hydrolysis reaction. A KH-560 silane coupling agent is then added to carry out a coupling reaction to obtain hydrophobically modified silicon dioxide-wrapped nano-iron particles.

[0071] In the present invention, the pH of the alkaline ethanol solution of the silica-encapsulated nano-iron particles is ≥ 8.5; the concentration of the silica-encapsulated nano-iron particles in the alkaline ethanol solution of the silica-encapsulated nano-iron particles is preferably 0.040-0.10 g / mL, more preferably 0.067 g / mL.

[0072] In the present invention, the conditions for the plasma modification treatment are preferably: the equipment is a plasma processor, the voltage is 30-45KV, the temperature is 80-90°C, the frequency is 300Hz, the time is 2-5min, the concentration of oxygen in the gas used is preferably 50vt%-70vt%, and the gas flow rate is 2-10L / min.

[0073] In the present invention, the temperature of the hydrolysis reaction is preferably 70-100°C, more preferably 75-95°C; the time of the hydrolysis reaction is preferably 3-7h, more preferably 4-5h. The present invention allows the Si-Cl bond in dimethyldichlorosilane DCDMS to fully react with the Si-(OH) bond in the nano-iron particles coated with silicon dioxide in toluene through the hydrolysis reaction to finally form a long chain structure with Si-O-Si bonds as the main link.

[0074] In the present invention, the mass ratio of the activated silica-wrapped nano-iron particles, dimethyldichlorosilane and KH-560 type silane coupling agent is preferably (20-80):100:(2-30), and more preferably (30-70):100:(10-26).

[0075] In the present invention, the temperature of the coupling reaction is preferably 50 to 70° C.; the time of the coupling reaction is preferably 6 to 10 hours.

[0076] After the coupling reaction is completed, the product of the coupling reaction is washed with toluene to obtain hydrophobically modified silica-coated nano-iron particles, referred to as H-SiO 2 @CIP particles.

[0077] In the present invention, the silicon dioxide-coated nano-iron particles are preferably purchased from the market or made at home.

[0078] In the present invention, the method for preparing the silicon dioxide-encapsulated nano-iron particles preferably comprises the following steps:

[0079] (T1) After pure water and carbonyl iron powder are stirred and mixed, a first turbid liquid is obtained by ultrasonication;

[0080] Mixing anhydrous ethanol, ethyl tetrasilicate and KH-560 silane coupling agent to obtain a second turbid liquid;

[0081] (T2) mixing the first turbid liquid obtained in step (T1) with the second turbid liquid, adding L-lysine catalyst, and performing heat treatment under stirring to obtain a mixture;

[0082] (T3) the mixture obtained in step (T2) is allowed to stand for stratification, the upper clear liquid is poured out, and the lower precipitate is washed 2 to 4 times with a 75% ethanol solution, and magnetic enrichment, vacuum drying and grinding are performed in sequence to obtain SiO 2 @CIP particles, that is, silica-encapsulated nano-iron particles.

[0083] In the present invention, the ultrasonic time is preferably 150 to 220 seconds. The present invention has no specific limitation on the ultrasonic time as long as the components are mixed evenly. In the present invention, the concentration of carbonyl iron powder in the first turbid solution is preferably 4wt% to 15wt%, more preferably 5wt% to 10wt%.

[0084] In the present invention, the concentration of ethyl tetrasilicate in the second turbid liquid is preferably 0.5wt% to 2wt%, more preferably 0.7wt% to 1.5wt%; the concentration of KH-560 type silane coupling agent in the second turbid liquid is preferably 0.5wt% to 2wt%, more preferably 0.8wt% to 1.6wt%.

[0085] In the present invention, the L-lysine catalyst preferably accounts for 0.2wt% to 1wt% of the first turbid liquid and the second turbid liquid, and more preferably 0.5wt% to 0.8wt%. In the present invention, the temperature of the heat treatment is preferably 43 to 58°C, and more preferably 45 to 55°C; the time of the heat treatment is preferably 2 to 7h, and more preferably 3 to 5h.

[0086] In the present invention, the vacuum drying temperature is preferably 70-80°C, and the vacuum drying time is preferably 18-25h, more preferably 20h. In the present invention, the particle size of the silicon dioxide-coated nano-iron particles is preferably 10-200nm, more preferably 20-150μm.

[0087] The present invention also provides the use of the net material with both anti-adhesion, self-cleaning and toughness as described in the above technical solution in the preparation of aquaculture nets, comprising the following steps:

[0088] A plurality of strands of the net material are braided to form a net rope, and the net rope is woven to form a knotless mesh sheet, so as to obtain a breeding net with anti-adhesion, self-cleaning and toughness.

[0089] In the present invention, the net material is preferably used as a monofilament of a net rope; the net rope is preferably prepared by weaving 3, 6 or 8 strands of the net material. The present invention uses weaving to prepare the net rope, avoiding the double-layer membrane structure material of the anti-adhesion surface of the monofilament surface being damaged by friction between the monofilaments due to the twisting method.

[0090] In the present invention, the mesh of the aquaculture net with anti-adhesion, self-cleaning and toughness is preferably one or more of square, rhombus and regular hexagon.

[0091] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0092] Some of the raw materials used in the examples and comparative examples of the present invention are as follows:

[0093] Polyethylene with a molecular weight of 250,000, produced by Guangzhou Yangu Trading Co., Ltd.;

[0094] PET resin with a molecular weight of 130,000, produced by DuPont in the United States;

[0095] The maleic anhydride grafted polyethylene is maleic anhydride grafted PE of model number ADDIMER 630R produced by CERONAS of Germany.

[0096] Example 1

[0097] A mesh material with both anti-adhesion, self-cleaning and toughness, including a three-layer structure, from the inside to the outside, respectively, an antibacterial polyethylene core layer, an ultra-thin strong magnetic film and an epoxy resin;

[0098] The diameter of the antibacterial polyethylene core layer is 1.5 mm, the thickness of the ultra-thin strong magnetic film is 100 μm and the surface has H-SiO 2 @The thickness of the epoxy resin layer of the CIP silane microstructure is 170 μm;

[0099] The preparation method of the net material comprises the following steps:

[0100] S1, preparing an antibacterial polyethylene core layer;

[0101] S2, using a coating machine and a polyurethane emulsion adhesive, tightly coating the surface of the antibacterial polyethylene core layer obtained in step (S1) with an ultra-thin strong magnetic film, and hot pressing at 150° C. for 1 min to obtain a coated antibacterial polyethylene core layer;

[0102] S3, coating the epoxy resin mixed solution on the surface of the coated antibacterial polyethylene core layer obtained in the step (S2), and drying to obtain a net material having both anti-adhesion, self-cleaning and toughness.

[0103] The method for preparing the antibacterial polyethylene core layer in step (S1) comprises the following steps:

[0104] (1) Premixing polyethylene, polyhexamethylene guanidine phosphate, streptomycin, succinic anhydride, and dicumyl peroxide, and uniformly blending them by rapid mechanical stirring and in a water bath at 180° C., and then grafting them at 200° C. for 4 h, and then extruding and granulating them to obtain antibacterial polymer particles with a particle size of 2 mm;

[0105] The total weight of the polyhexamethylene guanidine phosphate and streptomycin accounts for 20% of the weight of polyethylene; the weight of the succinic anhydride accounts for 10% of the weight of polyethylene; the weight of the dicumyl peroxide initiator accounts for 1.2% of the weight of the polyolefin;

[0106] (2) premixing the antibacterial polymer particles obtained in step (1) with a PET resin having a molecular weight of 300,000, a phenolic antioxidant, and polyethylene grafted with maleic anhydride, kneading at high speed for 1 hour, extruding and granulating, and melt-extruded from the spinneret holes of a spinneret by a single-screw extruder, and melt-spinning and stretching to obtain an antibacterial high-molecular polyethylene monofilament core body;

[0107] The mass ratio of the antibacterial polymer particles to the PET resin and the maleic anhydride grafted polyethylene is preferably 1:1.6:1.6; the mass of the phenolic antioxidant 2,6-di-tert-butyl-4-methylphenol accounts for 0.008% of the mass of the antibacterial polymer particles; the diameter of the spinneret hole is 1.5 mm; the process conditions of the melt spinning and stretching treatment are: the spinning temperature 2 is 40°C, the spinning speed is 10 m / min, the stretching multiple is 30 times, and the stretching temperature is 100°C;

[0108] The preparation method of the ultra-thin strong magnetic film in the step (S2) comprises the following steps: uniformly mixing 60 parts of polyethylene particles, 30 parts of carbonyl iron powder with a diameter of 3 nm and 3 parts of KH-560 silane coupling agent to obtain surface pre-treated particles; extruding and granulating the surface pre-treated particles in a twin-screw extruder to obtain master batches; processing the master batches through a blow molding machine to obtain an ultra-thin strong magnetic film;

[0109] The parameters of the twin-screw extruder are preferably: heating temperature of 120-190°C, screw speed of 240r / min, and feeding speed of 55r / min; the parameters of the blow molding machine are preferably: heating temperature of 120-210°C, screw speed of 110r / min, blow-up ratio of 1:2, and traction speed of 6m / min;

[0110] The step (S3) is specifically:

[0111] (S3-1) 10g H-SiO 2 @CIP was placed in 100 mL of ethyl acetate as a diluent and subjected to ultrasonic treatment to form an ethyl acetate suspension of hydrophobically modified silica-encapsulated nano-iron particles;

[0112] PDMS with a molecular weight of 3000, a methyltri(methoxy)silane crosslinking agent, and an ethyl acetate suspension of the hydrophobically modified silica-encapsulated nano-iron particles are mixed and stirred in a fume hood to fully volatilize the ethyl acetate, and then vacuum defoamed and ultrasonically treated for 15 minutes to obtain a mixed solution;

[0113] The mass ratio of the polydimethylsiloxane, methyltri(methoxy)silane crosslinking agent, and the hydrophobically modified silica-wrapped nano-iron particles is 15:5:10;

[0114] The mixed solution and bisphenol A epoxy resin are mixed, stirred by a single-screw machine for 45 minutes, and then subjected to vacuum defoaming treatment to obtain a mixed solution containing bisphenol A epoxy resin;

[0115] The concentration of bisphenol A epoxy resin in the mixed solution containing bisphenol A epoxy resin is 60wt%;

[0116] (S3-2) Spin-coating the mixed solution containing bisphenol epoxy resin obtained in step (S3-1) on the surface of the coated antibacterial polyethylene core layer obtained in step (S2) to form a 180 μm coating, and drying it in a ventilated drying oven at 50° C. for 18 hours to obtain a net material with both anti-adhesion, self-cleaning and toughness;

[0117] In the step (S3-1), the hydrophobically modified silica encapsulates the nano-iron particles (i.e., H-SiO 2 @CIP) preparation method, the steps are as follows:

[0118] First, prepare silicon dioxide-encapsulated nano-iron particles, namely SiO 2 @CIP particles, the steps are as follows:

[0119] (T1) adding carbonyl iron powder to pure water, stirring and mixing, and ultrasonicating for 180 seconds to obtain a first turbid solution;

[0120] The concentration of carbonyl iron powder in the first turbid liquid is 7wt%;

[0121] Adding ethyl tetrasilicate and KH-560 silane coupling agent into anhydrous ethanol and mixing to obtain a second turbid liquid;

[0122] The concentration of ethyl tetrasilicate in the second turbid liquid is 1wt%; the concentration of KH-560 silane coupling agent in the second turbid liquid is 1.5wt%;

[0123] (T2) mixing the first turbid liquid and the second turbid liquid obtained in step (T1), adding catalyst L-lysine, stirring with a magnetic stirrer, and heat treating in a constant temperature water bath at 48° C. for 4 h to obtain a mixture;

[0124] The L-lysine catalyst accounts for 0.5wt% of the total amount of the first turbid liquid and the second turbid liquid;

[0125] (T3) The mixture obtained in step (T2) was allowed to stand for stratification, the upper clear liquid was poured out, and the lower precipitate was washed 4 times with a 75% ethanol solution, magnetically enriched using a block magnet, and then vacuum dried at 80° C. for 20 h, and SiO2 with a particle size of 20 μm was obtained by grinding. 2 @CIP particles;

[0126] 3g of SiO prepared by the above method was 2 @CIP particles were mixed with 45 mL of alkaline ethanol solution with a pH of 9 to make SiO 2 The particle surface is fully hydroxylated.

[0127] Then, after drying in the fume hood, the SiO 2 @CIP uses plasma modification to produce active hydroxyl functional groups on its surface, obtaining activated silica-coated nano-iron particles;

[0128] The conditions of the plasma modification treatment are preferably: the equipment is a plasma treatment machine, the voltage is 36KV, the temperature is 90°C, the frequency is 300Hz, the time is 3min, the concentration of oxygen in the gas used is preferably 60vt%, and the gas flow rate is 4L / min;

[0129] The activated silica-coated nano-iron particles were mixed with toluene and DCDMS, and the mixture was hydrolyzed at 80°C for 5 h. 0.2 mL of KH-560 was added by pipette, and then the coupling reaction was carried out at 60°C for 8 h to promote the SiO 2 @CIP surface long chain structure coupling, repeated washing with toluene solution to remove the reaction residues, and finally obtain H-SiO 2 @CIP particles.

[0130] Example 2

[0131] A mesh material with anti-adhesion, self-cleaning and toughness, which is different from Example 1 in that: in the step (S3-2), the mixed liquid containing bisphenol epoxy resin obtained in the step (S1) is spin-coated on the surface of the coated antibacterial polyethylene core layer to form a 150μm coating.

[0132] Example 3

[0133] A mesh material with anti-adhesion, self-cleaning and toughness, which is different from Example 1 in that: in the step (S3-2), the mixed liquid containing bisphenol epoxy resin obtained in the step (S1) is spin-coated on the surface of the coated antibacterial polyethylene core layer to form a 200 μm coating.

[0134] Application Example 1

[0135] A net for breeding is prepared by using the net material with anti-adhesion, self-cleaning and toughness prepared in Example 1 as monofilament, and the steps are as follows:

[0136] The six strands of the monofilaments are braided to form a net rope, and the net rope is woven to form a knotless mesh with regular hexagonal meshes, so as to obtain a breeding net with anti-adhesion, self-cleaning and toughness.

[0137] Application Example 2

[0138] A net for breeding is prepared by using the net material with anti-adhesion, self-cleaning and toughness prepared in Example 2 as monofilament, and the steps are as follows:

[0139] The six strands of the monofilaments are braided to form a net rope, and the net rope is woven to form a knotless mesh with regular hexagonal meshes, so as to obtain a breeding net with anti-adhesion, self-cleaning and toughness.

[0140] Application Example 3

[0141] A net for breeding is prepared by using the net material with anti-adhesion, self-cleaning and toughness prepared in Example 3 as monofilament, and the steps are as follows:

[0142] The six strands of the monofilaments are braided to form a net rope, and the net rope is woven to form a knotless mesh with regular hexagonal meshes, so as to obtain a breeding net with anti-adhesion, self-cleaning and toughness.

[0143] Comparative Example 1

[0144] A net material, which is different from that of Example 1 in that it only has an antibacterial polyethylene core layer;

[0145] Then, the net material is used according to the method of Application Example 1 to prepare a net for breeding.

[0146] Comparative Example 2

[0147] A net material, which is different from that of Example 1 in that it only has an antibacterial polyethylene core layer and an ultra-thin strong magnetic film;

[0148] Then, the net material is used according to the method of Application Example 1 to prepare a net for breeding.

[0149] Comparative Example 3

[0150] A net material, which is different from Example 1 in that: the outer surface of the epoxy resin layer is not constructed with a hydrophobically modified silica-coated nano-iron particle-silane microstructure, that is, when preparing the epoxy resin mixed solution, no hydrophobically modified silica-coated nano-iron particle H-SiO 2 @CIP;

[0151] Then, the net material is used according to the method of Application Example 1 to prepare a net for breeding.

[0152] The breaking strength of the aquaculture nets with anti-adhesion, self-cleaning and toughness prepared in Application Examples 1 to 3 and the aquaculture nets prepared in Comparative Examples 1 to 3 was tested; and the antifouling performance was evaluated after hanging the nets in the actual sea. If the area of ​​marine fouling attached on the net is less than 10%, the antifouling coating is considered to be effective. The test results are shown in Table 1.

[0153]

[0154]

[0155] As shown in Table 1, the anti-adhesion and self-cleaning properties of the invention prepared in Application Examples 1 to 3 have an anti-fouling effect of up to 26 months, a corrosion rate as low as 3.3 μm / month, and a breaking strength of 9.7 g / D.

[0156] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A net material with both anti-adhesion, self-cleaning and toughness, characterized in that: It consists of three layers, from the inside to the outside, namely, an antibacterial polyethylene core layer, an ultra-thin strong magnetic film, and an epoxy resin layer with H-SiO2@CIP silane microstructure on the surface; The preparation method of the net material comprises the following steps: S1, preparing an antibacterial polyethylene core layer; S2, coating the antibacterial polyethylene core layer obtained in step (S1) with the ultra-thin ferromagnetic film to obtain a coated antibacterial polyethylene core layer; S3, coating the epoxy resin mixed solution on the surface of the coated antibacterial polyethylene core layer obtained in the step (S2), and drying to obtain a net material having both anti-adhesion, self-cleaning and toughness.

2. The net material with both anti-adhesion, self-cleaning and toughness according to claim 1, characterized in that: The diameter of the antibacterial polyethylene core layer is 1-3.5 mm, the thickness of the ultra-thin strong magnetic film is 2-400 μm, and the thickness of the epoxy resin layer with H-SiO2@CIP silane microstructure on the surface is 80-260 μm.

3. The net material with both anti-adhesion, self-cleaning and toughness according to claim 1 or 2, characterized in that: The method for preparing the antibacterial polyethylene core layer in step (S1) comprises the following steps: (1) premixing polyethylene, an antibacterial agent, succinic anhydride and dicumyl peroxide, and then sequentially performing blending, grafting reaction and extrusion granulation to obtain antibacterial polymer particles; (2) The antibacterial polymer particles obtained in step (1) are premixed with PET resin, phenolic antioxidant, and maleic anhydride grafted polyethylene, and then kneaded and extruded into granules in sequence, and then melt-extruded from the spinneret holes of a spinneret by a single-screw extruder, and melt-spinned and stretched to obtain an antibacterial polyethylene core layer.

4. The net material with both anti-adhesion, self-cleaning and toughness according to claim 3, characterized in that: In the step (1), the antibacterial agent is at least two of polyhexamethylene monoguanidine phosphate, polyhexamethylene biguanidine phosphate, and streptomycin.

5. The net material with both anti-adhesion, self-cleaning and toughness according to claim 1, characterized in that: The step (S3) comprises the following steps: (S3-1) mixing a suspension of polydimethylsiloxane, a crosslinking agent and nano-iron particles coated with hydrophobically modified silica, and then sequentially performing a first stirring, a first vacuum degassing and an ultrasonic treatment to obtain a mixed solution; Adding bisphenol epoxy resin to the mixed solution, and sequentially performing a second stirring and a second vacuum defoaming to obtain an epoxy resin mixed solution; (S3-2) coating the epoxy resin mixed solution obtained in the step (S3-1) on the surface of the coated antibacterial polyethylene core layer obtained in the step (S2), and drying to obtain a mesh material having anti-adhesion, self-cleaning and toughness.

6. The net material with both anti-adhesion, self-cleaning and toughness according to claim 5, characterized in that: The method for preparing the hydrophobically modified silica-encapsulated nano-iron particles in step (S3-1) comprises the following steps: The silicon dioxide-coated nano-iron particles are dispersed in an alkaline ethanol solution, dried, and then subjected to plasma modification treatment to obtain activated silicon dioxide-coated nano-iron particles; The activated silicon dioxide-wrapped nano-iron particles are mixed with dimethyldichlorosilane and toluene, and then subjected to a hydrolysis reaction. A KH-560 silane coupling agent is then added to carry out a coupling reaction to obtain hydrophobically modified silicon dioxide-wrapped nano-iron particles.

7. The net material with both anti-adhesion, self-cleaning and toughness according to claim 6, characterized in that: The time of the plasma modification treatment is 2 to 5 minutes, and the concentration of oxygen in the gas used for the plasma modification treatment is 50 vt% to 70 vt%.

8. The net material with both anti-adhesion, self-cleaning and toughness according to claim 5, characterized in that: In the step (S3-1), the mass ratio of polydimethylsiloxane, crosslinking agent, and hydrophobically modified silica-wrapped nano-iron particles is 15:(2-8):(6-12).

9. The net material with both anti-adhesion, self-cleaning and toughness according to claim 5, characterized in that: The drying temperature in the step (S3-2) is 45 to 55°C, and the drying time is 16 to 20 hours.

10. Use of the net material having both anti-adhesion, self-cleaning and toughness according to any one of claims 1 to 9 in preparing nets for breeding, characterized in that: The following steps are involved: A plurality of strands of the net material are braided to form a net rope, and the net rope is woven to form a knotless mesh sheet, so as to obtain a breeding net with anti-adhesion, self-cleaning and toughness.

Citation Information

Patent Citations

  • Method for preparing super-hydrophobic nano-magnetic thin film

    CN102336972A

  • Super-hydrophobic super-oleophylic oil-water separation mesh membrane with self-cleaning function and preparation method thereof

    CN105214344A

  • Strong-acid-resistant magnetic adsorption particle

    CN106622175A

  • Magnetic particles and manufacturing process thereof

    CN113707403A

  • Aquaculture antifouling netting and preparation method thereof

    CN118516781A

Cited By

  • Thin film material with anti-fouling function as well as preparation method and application of thin film material

    CN120307745A